PENGGUNAAN PROGRAM LINEAR DAPAT MENINGKATKAN OPTIMALISASI LABA PADA PT. LILIN BODI DI MAKASSAR - Mihrani Mihrani (Lembaga Penelitian, Publikasi dan Pengabdian pada Masyarakat (LP3M) Nobel Indonesia, 2016)
The results showed that, if the company produces jumbo Candles (X1) of 2.424,2 rods and Candles being (X2) from 0 cigarettes per day, the maximum profit is generated Rp. 1.87367 million per day. Furthermore, if the company produces small wax combination (X1) of 2857.1 rod and jumbo Candles (X2) from 0 cigarettes per day, the maximum profit is generated Rp. 1.87497 million. Beside that, if the company produces a combination of moderate Candles (X1) of 1818.2 stems and small candles (X2) from 0 cigarettes per day, the maximum profit is generated Rp. 152 950 per day. Among the two models proposed combination of the author, it turns out the combination of products that can generate the most optimal profit contribution that is a combination of small candles (X1) of 2. 875.1 rod and jumbo Candles (X2) 0 cigarettes per day with a value of over Rp. 1.87497 million per day. So the hypothesis that profit optimization using linear programming, can prove to the PT. Lilin Bodi in Makassar